The relationship of perceptions of tap water safety with intake of sugar-sweetened beverages and plain water among US adults. Issue 1 (26th October 2012) - Onufrak, Stephen J; Park, Sohyun; Sharkey, Joseph R; Sherry, Bettylou
Abstract: Objective: Research is limited on whether mistrust of tap water discourages plain water intake and leads to a greater intake of sugar-sweetened beverages (SSB). The objective of the present study was to examine demographic differences in perceptions of tap water safety and determine if these perceptions are associated with intake of SSB and plain water. Design: The study examined perceptions of tap water safety and their cross-sectional association with intake of SSB and plain water. Racial/ethnic differences in the associations of tap water perceptions with SSB and plain water intake were also examined. Setting: Nationally weighted data from the 2010 HealthStyles Survey ( n 4184). Subjects: US adults aged ≥18 years. Results: Overall, 13·0 % of participants disagreed that their local tap water was safe to drink and 26·4 % of participants agreed that bottled water was safer than tap water. Both mistrust of tap water safety and favouring bottled water differed by region, age, race/ethnicity, income and education. The associations of tap water mistrust with intake of SSB and plain water were modified by race/ethnicity ( P < 0·05). Non-white racial/ethnic groups who disagreed that their local tap water was safe to drink were more likely to report low intake of plain water. The odds of consuming ≥1 SSB/d among Hispanics who mistrusted their local tap water was twice that of Hispanics who did not (OR = 2·0; 95 % CI 1·2, 3·3). Conclusions: Public health efforts to promote healthy beverages should recognize the potential impact of tap water perceptions on water and SSB intake among minority populations.